Pluralitas Agama di Kota Malang dan Dialog Gereja Terhadapnya - Simamora, Chandra Susilo (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2019)
Indonesia is a plural society, particularly in the religious aspect. It is very prominent all over the Indonesian islands and cities, including the city of Malang. Plurality in religion of this city, on the one hand, contributes for the richness of living together besides its differences. On the other hand, it brings forth some problems, particularly the issue of majority-minority relationship. For bridging the gap, the Catholic Church of the Diocese of Malang has always been promoting interreligious dialogue with people of other faiths. The writer reflects this bridge-building in the light of Jacques Dupuis’ theology of dialogue and Trinitarian Christology that may enrich the practice of interreligious dialogue throughout the city.